TRANSPARANSI DAN AKUNTABILITAS ALOKASI DANA DESA (Studi pada Desa Trimulyo, Kecamatan Jetis, Kabupaten Bantul Tahun 2015) - Eni Dwi Susliyanti (Akademi Akuntansi YKPN Yogyakarta, 2017)
Financial management village is one important issue for starting in 2015 since all villageswill receive village funds allocation of 1 billion. The implications of the the village funds allocationencourage the village to make planning, management and evaluation the program in transparent andaccountable. The purpose of this study is to describe the system transparency and accountability ofvillage funds allocation and to measure whether realization of this implemented effectively and thenumber of contribution. Technique data collection in this research is by interviews, direct observationand analysis documents.The result showed planning and the implementation of village funds allocation in DistrictTrimulyo, Jetis Bantul had to apply the principle of partisipasif, transparency and accountability. Theprocess of reporting this have proven by accountability which done periodically. Village fundsallocation in District Trimulyo was very effective as much as 100 % in addition the contribution ofratio is 55,62 % of the total income received.Keywords: Village Fund Allocation (ADD), Transparency, Accountability, Effectivity andContribution.